Identification of Differentially Expressed Gene Transcripts in Porcine Endometrium during Early Stages of Pregnancy - Mariusz Pierzchała; Dorota Pierzchała; Magdalena Ogłuszka; Ewa Poławska; Tadeusz Blicharski; Agnieszka Roszczyk; Agata Nawrocka; Pawel Urbański; Kamila Stepanow; Aleksandra Ciepłoch; Agnieszka Korwin-Kossakowska; Marinus F.W. te Pas; et al. (Life, 2020)
During the early stages of pregnancy, the uterine endometrium undergoes dramatic morphologic and functional changes accompanied with dynamic variation in gene expression. Pregnancy-stage specific differentially expressed gene (DEG)-transcript-probes were investigated and identified by comparing endometrium transcriptome at 9th day (9D), 12th day (12D) and 16th day (16D) of early pregnancy in Polish large-white (PLW) gilts. Endometrium comparisons between 9D-vs-12D, 9D-vs-16D and 12D-vs-16D of early pregnancy identified 6049, 374 and 6034 highly significant DEG-transcript-probes (p < 0.001; >2 FC). GO term enrichment analysis identified commonly shared upregulated endometrial DEG-transcript-probes (p < 0.001; >2 FC), that were regulating the gene functions of anatomic structure development and transport (TG), DNA-binding and methyltransferase activity (ZBTB2), ion-binding and kinase activity (CKM), cell proliferation and apoptosis activity (IL1B). Downregulated DEG-transcript-probes (p < 0.001; >2 FC) were involved in regulating the gene functions of phosphatase activity (PTPN11), TC616413 gene-transcript and Sus-scrofa LOC100525539. Moreover, blastn comparison of microarray-probes sequences against sus-scrofa11 assembly identified commonly shared upregulated endometrial DEG-transcript-probes (E < 0.06; >2 FC), that were regulating the gene functions of reproduction and growth (SELENOP), cytoskeleton organization and kinase activity (CDC42BPA), phosphatase activity (MINPP1), enzyme-binding and cell-population proliferation (VAV3), cancer-susceptibility candidate gene (CASC4), cytoskeletal protein-binding (COBLL1), ion-binding, enzyme regulator activity (ACAP2) Downregulated endometrial DEG-transcript-probes (E < 0.06; >2FC) were involved in regulating the gene functions of signal-transduction (TMEM33), catabolic and metabolic processes (KLHL15). Microarray validation experiment on selected candidate genes showed complementarity to significant endometrial DEG-transcript-probes responsible for the regulation of immune response (IL1B, S100A11), lipid metabolism (FABP3, PPARG), cell-adhesion (ITGAV), angiogenesis (IL1B), intercellular transmission (NMB), cell-adhesion (OPN) and response to stimuli (RBP4) was confirmed by RT-PCR. This study provides a clue that identified pregnancy-stage specific microarray transcript probes could be considered as candidate genes for recognition and establishment of early pregnancy in the pig.